Building Climate Resilient Agriculture in Caribbean Countries: St. Kitts and Nevis - Hayman, Alicia A (Instituto Interamericano de Cooperación para la Agricultura (IICA), 2023)
St. Kitts & Nevis' agriculture sector represents 1.4% of GDP and consists of small-scale farms. The government owns most of the farm land, with the remainder owned by individuals and families. Subsistence farming is common, and policies support increased production for domestic food supply. However, the Agriculture Transformation and Growth Strategy (2022) and adaptation projects offer opportunities for building CRA and enhancing climate ambition in the Nationally Determined Contributions. The Greenhouse Gas inventory also provides options and opportunities for prioritizing CRA projects.